2011
DOI: 10.1056/nejmoa1102077
|View full text |Cite|
|
Sign up to set email alerts
|

Decompressive Craniectomy in Diffuse Traumatic Brain Injury

Abstract: In adults with severe diffuse traumatic brain injury and refractory intracranial hypertension, early bifrontotemporoparietal decompressive craniectomy decreased intracranial pressure and the length of stay in the ICU but was associated with more unfavorable outcomes. (Funded by the National Health and Medical Research Council of Australia and others; DECRA Australian Clinical Trials Registry number, ACTRN012605000009617.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
763
4
29

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,352 publications
(857 citation statements)
references
References 33 publications
22
763
4
29
Order By: Relevance
“…Some practices, such as the use of hypothermia in TBI patients, decompressive craniectomy, and ICP monitoring, have been reported to lack efficacy at improving outcomes in preliminary clinical trials. [44][45][46] Nevertheless, our findings are in agreement with multiple observational studies suggesting that the development of specialized neurocritical care unitsusually supported by the presence of neurointensivists and utilizing evidence-based protocols-may contribute to improved patient outcomes. 28 International studies involving neurocritical care patients have suggested that there is considerable variability in outcomes between countries and individual centers.…”
Section: Discussionsupporting
confidence: 90%
“…Some practices, such as the use of hypothermia in TBI patients, decompressive craniectomy, and ICP monitoring, have been reported to lack efficacy at improving outcomes in preliminary clinical trials. [44][45][46] Nevertheless, our findings are in agreement with multiple observational studies suggesting that the development of specialized neurocritical care unitsusually supported by the presence of neurointensivists and utilizing evidence-based protocols-may contribute to improved patient outcomes. 28 International studies involving neurocritical care patients have suggested that there is considerable variability in outcomes between countries and individual centers.…”
Section: Discussionsupporting
confidence: 90%
“…These findings may have been influenced by the "early" timing of craniectomy in their protocols, potentially averting secondary brain damage associated with cerebral edema [47], although the inclusion of patients who may not have truly needed decompression also may have favorably influenced outcome. In contrast, worse outcomes were reported for decompressive craniectomy in traumatic brain injury when compared to maximal medical therapy alone [48]. However, applicability of these findings is tempered based on choice of operative technique (bifrontal procedure), a long study accrual time, differences in study arms (significantly more patients with bilaterally unreactive pupils included in the surgical group), and minimal mean elevations in intracranial pressure leading up to randomization.…”
Section: Osmotherapymentioning
confidence: 97%
“…In addition to improving ICP, DC has also been shown to improve cerebral oxygenation in pediatric patients with TBI [75,99]. The recently published "Decompressive Craniectomy in Diffuse TBI" and the Randomised Evaluation of Surgery with Craniectomy for Uncontrollable Elevation of Intra-Cranial Pressure (RESCUEicp) trials in adults may lay the groundwork for a similar study to be performed with pediatric patients [100]. Large, randomized trials in pediatric patients that address long-term outcomes, including quality of life measures, are needed to address optimal patient selection, timing of intervention, and surgical methods.…”
Section: Decompressive Craniectomymentioning
confidence: 99%